ANALISIS PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL DAN KECERDASAN INTELEKTUAL TERHADAP SELF EFFICACY DAN KINERJA GURU SEKOLAH DARMA YUDHA PEKANBARU - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2022)
Employee performance problems always attract interest to be studied, because employee performance is the spearhead for measuring the achievement of company goals. The success in achieving the goals of a company is very much determined by the workforce factor who has adequate work performance, especially in the current intense business competition. Likewise in schools that are engaged in educational services, where the contact between students and educators is relatively intensive, the self-efficacy of educators is one of the key factors determining school success. The purpose of this study was to examine the influence of Emotional Intelligence, Spiritual Intelligence, and Intellectual Intelligence on Self Efficacy and Teacher Performance at Darma Yudha School Pekanbaru. The respondents of this research were 70 teachers. As exogenous variables are Emotional Intelligence, Spiritual Intelligence, and Intellectual Intelligence. While the endogenous variables consist of Self Efficacy and Teacher Performance. The analytical tool used in this research is path analysis using PLS-SEM. The results of the hypothesis test show that Emotional Intelligence has no significant effect on Self Efficacy and Teacher Performance, while Spiritual Intelligence, Intellectual Intelligence has a significant effect on Self Efficacy and Teacher Performance. For the Self Efficacy variable has a significant effect on teacher performance. The results of this study suggest that schools socializing school values ​​through socialization or seminars on teacher career development will be able to motivate and provide a clear picture of the main duties and functions of teachers.   Permasalahan kinerja karyawan selalu menarik minat untuk dikaji, karena kinerja karyawan merupakan ujung tombak untuk mengukur pencapaian tujuan perusahaan. Keberhasilan pencapaian tujuan suatu perusahaan sangat ditentukan oleh faktor tenaga kerja yang mempunyai prestasi kerja yang memadai, apalagi dalam persaingan bisnis yang ketat seperti saat ini. Demikian juga halnya pada sekolah yang bergerak di bidang jasa pendidikan, dimana kontak antara murid dan tenaga pendidik relatif intensif, self efficacy tenaga pendidik menjadi salah satu faktor kunci penentu keberhasilan sekolah. Tujuan penelitian ini adalah untuk menguji pengaruh Kecerdasan Emosional, Kecerdasan Spiritual, dan Kecerdasan Intelektual terhadap Self Efficacy dan Kinerja Guru Sekolah Darma Yudha Pekanbaru. Responden penelitian ini adalah guru sebanyak 70 orang. Sebagai variabel eksogen adalah Kecerdasan Emosional, Kecerdasan Spiritual, dan Kecerdasan Intelektual. Sedangkan variabel endogen terdiri atas Self Efficacy dan Kinerja Guru. Alat analisis yang akan digunakan dalam penelitian ini adalah path analysis dengan penggunakan PLS-SEM. Hasil uji hipotesis menunjukkan bahwa Kecerdasan Emosional tidak signifikan berpengaruh terhadap Self Efficacy dan Kinerja Guru sedangkan Kecerdasan Spiritual, Kecerdasan Intelektual signifikan berpengaruh terhadap Self Efficacy dan Kinerja Guru. Untuk variabel Self Efficacy signifikan berpengaruh terhadap Kinerja Guru. Hasil penelitian ini menyarankan agar sekolah mensosialisasikan nilai-nilai sekolah melalui sosialisasi atau seminar tentang pengembangan karir guru akan dapat memotivasi dan memberikan gambaran yang jelas tentang tugas pokok dan fungsi guru.